2014
DOI: 10.1016/j.jvs.2013.07.025
|View full text |Cite
|
Sign up to set email alerts
|

The need for treatment of hemodynamic instability following carotid endarterectomy is associated with increased perioperative and 1-year morbidity and mortality

Abstract: Objective The objective of this study was to evaluate the outcomes of patients after carotid endarterectomy (CEA) who developed postoperative hypertension or hypotension requiring the administration of intravenous vasoactive medication (IVMED). Methods We examined consecutive, primary elective CEA performed by 128 surgeons within the Vascular Study Group of New England (VSGNE) database (2003-2010) and compared outcomes of patients who required postoperative IVMED to treat hyper- or hypotension with those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 37 publications
1
29
1
1
Order By: Relevance
“…22 Indeed, both postoperative hypertension and hypotension have been associated with cardiac complications in a VQI study using a regional data set. 23 In sum, these findings justify close monitoring of CEA patients in the postoperative period.…”
Section: Discussionmentioning
confidence: 75%
“…22 Indeed, both postoperative hypertension and hypotension have been associated with cardiac complications in a VQI study using a regional data set. 23 In sum, these findings justify close monitoring of CEA patients in the postoperative period.…”
Section: Discussionmentioning
confidence: 75%
“…[25] Post-operative hemodynamic instability after CEA is a well-described phenomenon presenting a major barrier to post-operative day one discharge. [6, 7, 26-28] In our CEA population, post-operative hypertension or hypotension affects over 25% and 10% of our patients requiring prolonged LOS respectively. This is a major target for improvement as we have advancements in intraoperative monitoring and anesthetic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A recent analysis showed that adequate implementation of 2014 hypertension guidelines could potentially prevent 37,400 strokes annually in the U.S. 1 Haemodynamic instability is observed in 13% -23% of patients undergoing carotid endarterectomy (CEA) 2,3,4, and is associated with poor perioperative outcomes as well as an increased 1-year stroke or death rate. 3,4 Peri-procedural haemodynamic depression in patients treated by carotid artery stenting (CAS), is associated with an excess of new ischaemic brain lesions. In general, patients undergoing carotid intervention under general anaesthesia are more likely to be exposed to intra-procedural hypotension and post-procedural hypertension.…”
Section: Introductionmentioning
confidence: 99%